Management of massive hemopericardium in the electrophysiology laboratory: The double long sheath technique. Issue 5 (25th March 2022) - Chokr, Muhieddine Omar; Santos, Italo Bruno dos Santos Sousa; Gouvea, Fabio Cesar; Kulchetscki, Rodrigo; Andere, Tamer El; Hardy, Carina; Pisani, Cristiano; Melo, Sissy; Scanavacca, Mauricio
Abstract: Aim: To describe a simple and useful technique for acute management of massive hemopericardium inside the Electrophysiology (EP) laboratory Methods and results: Five patients from a single center experience were identified, all with blood loss above 1000 ml after initial pericardiocenthesis. Using two long 8.5 F transseptal sheaths inside the pericardium space, with continuous negative pressure, allowed the complete cessation of bleeding or hemodynamic maintenance until definitive surgical repair in all patients Conclusion: The use of two long sheaths for blood drainage, instead of conventional pericardiocenthesis, might be helpful to manage massive hemopericardium inside EP lab, avoiding urgent cardiac surgery or maintaining clinical stability until surgical staff is available.